2017
DOI: 10.1111/oik.04512
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic effects of the nurse Thylacospermum caespitosum on dependent plant species along regional climate stress gradients

Abstract: Contrasting phenotypes of alpine cushion species have been recurrently described in several mountain ranges along small‐scale topography gradients, with tight competitive phenotypes in stressful convex topography and loose facilitative phenotypes in sheltered concave topography. The consistency of phenotypic effects along large‐scale climate stress gradients have been proposed as a test of the likely genetic bases of the differences observed at small‐scale. Inversely, plastic phenotypic effects are more likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 61 publications
(118 reference statements)
4
21
0
1
Order By: Relevance
“…To properly capture not only the continuous nature of the measured variable but also its variation with time and space, intraspecific trait variability should be included in the study of plant facilitation networks (Poisot et al ., 2015). For example, some studies have shown that a single nurse species may have different phenotypes that have very contrasting effects on their facilitated plants (Michalet et al ., 2011; Jiang et al ., 2018; Pistón et al ., 2018). To capture the intraspecific temporal variation of traits is especially problematic for seedlings, which have fast growing rates and it is hard to determine when to measure them (Butterfield and Briggs, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…To properly capture not only the continuous nature of the measured variable but also its variation with time and space, intraspecific trait variability should be included in the study of plant facilitation networks (Poisot et al ., 2015). For example, some studies have shown that a single nurse species may have different phenotypes that have very contrasting effects on their facilitated plants (Michalet et al ., 2011; Jiang et al ., 2018; Pistón et al ., 2018). To capture the intraspecific temporal variation of traits is especially problematic for seedlings, which have fast growing rates and it is hard to determine when to measure them (Butterfield and Briggs, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…(), and Jiang et al. () stressed the importance of above‐ground traits—in particular canopy compactness—to explain the negative effects of tight phenotypes as compared to loose ones on associated species, although Schöb et al. () showed opposite effects.…”
Section: Introductionmentioning
confidence: 99%
“…Tighter phenotypes have been shown to reduce temperature and light but increase soil moisture and litter compared to loose phenotypes (Classen, Chapman, Whitham, Hart, & Koch, 2007;Crutsinger, Strauss, & Rudgers, 2010). Michalet et al (2011), Al Hayek et al (2015b), Bonanomi et al (2016), and Jiang et al (2018) stressed the importance of above-ground traits-in particular canopy compactness-to explain the negative effects of tight phenotypes as compared to loose ones on associated species, although Schöb et al (2013) showed opposite effects.…”
mentioning
confidence: 99%
“…They explained this interesting result by species pool effects, especially the lack of stress‐intolerant species under the most extreme conditions of stress. Similar species pool effects have also been shown to potentially affect the shape of the relationship between plant–plant interactions and environmental severity in salt marsh communities (Pennings, Selig, Houser, & Bertness, ), desert systems (Noumi, Chaieb, Michalet, & Touzard, ) and alpine communities (Jiang et al., ).…”
Section: Discussionmentioning
confidence: 83%